IMPROVING STUDENTS’ WRITING SKILLS IN DESCRIPTIVE TEXT USING PICTURE WORD INDUCTIVE MODEL (PWIM) STRATEGY - Oktafiani, Desy; Husnussalam, Hendra (PROJECT (Professional Journal of English Education), 2021)
The objective of the study is to provide the students treatment and make the students easy in learning process of writing descriptive text, therefore to improve the students writing skills in English by using PWIM strategy. The participants are the 7th grade students of Junior High School at Cimahi in academic year 2019/2020 which consist of 32 students. The study using CAR with two cycles to observe the activities and responses of students in classroom. Result of the study could be seen from the improvement score from pretest to posttest 2 with a minimum score of 75 and maximum score of 85 in posttest 2. Keywords:  Writing, Descriptive Text, PWIM Strategy, CAR